O3-S1.02 Deciphering the code of Treponema pallidum in the UK: implications for treatment and prevention. (10th July 2011) - Tipple, C; Taylor, G
Abstract : Background: The efficacy and convenience of single-dose oral azithromycin meant it became the preferred treatment for syphilis in many countries and a suitable alternative to penicillin in many more. However, two point mutations (A2058G and A2059G) in the 23srRNA gene of Treponema pallidum ( T pallidum ) have separately been shown to confer high-level macrolide resistance. Furthermore, molecular analyses of T pallidum with an enhanced sub-typing method have revealed the existence of a number of strain types, which both persist over generations and may be associated with distinct clinical phenotypes. Methods: Following informed consent, whole EDTA blood and ulcer exudate absorbed onto filter paper Snostrips were collected from patients with any stage of syphilis in a London genito-urinary medicine clinic between 2006 and 2008. T pallidum DNA was extracted and strain types and macrolide resistance-associated mutations sought by: (1) PCR amplification of the 23srRNA gene and restriction fragment length polymorphism (RFLP) analysis following Mbo-II and Bsa-I digestion; (2) determination of the number of 60-base repeats within the ARP gene by PCR and agarose gel electrophoresis; (3) PCR amplification of the TPR gene family and RFLP analysis following Mse-I digestion; (4) sequence analysis of a section of the tp548 gene. Results: Forty-two of the 44 (95.5%) patients diagnosed with syphilis were male, of which 63.6% were MSM and 28/44 (63.6%) were HIV-1 infected. T pallidum DNA was present in sufficient quantity and quality for analysis in 18/44 (40.9%). 23srRNA gene analysis revealed 6/18 (33.3%) wild-type sequences, 11/18 (61.1%) A2058G mutants and 1 (5.6%) A2059G mutant. Full strain-typing was possible in 5 clinical samples (four were 14d/g and one was 14d/f), and partial typing in a further 7 (see Abstract O3-S1.02 table 1 ). Conclusions: The high frequency of T pallidum macrolide resistance mutations described in the UK for the first time has clear implications for national treatment strategies. The majority of patients with syphilis were men, of which most were MSM and over half were HIV-1 positive. It is thought that transmission of T pallidum within sexual networks has played a part in the resurgence of syphilis in the UK over the last decade and the predominance of the 14d/g subtype may reflect this. Alternative explanations are that this strain type is more virulent or has become endemic, as in the case of the Scottish data that revealed 77% of syphilis cases there to be type 14d.